2015
DOI: 10.5322/jesi.2015.24.6.763
|View full text |Cite
|
Sign up to set email alerts
|

Establish of Optimum Cultivation Temperature for the Production of Peanut Sprouts

Abstract: The present study was conducted to development mass production methods for peanut sprouts that is considered as a field of blue ocean among the agricultural products. 'Jopyeong' was the best as a major cultivar for peanut sprouts production. The manual for the production of high-quality peanut sprouts is as following. Germination temperature appropriate for production of high-quality peanut sprouts was 27℃. Peanut sprouts at the growth stage of 8th day, and older plants with advanced growth showed deteriorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The results showed that peanut cultivars and breeding lines having smaller seed size or rapid growth rate could be economically efficient for getting higher sprout yields. Some of the cultivars and breeding lines had excessive sprout growth on day 8 and 9 which showed deteriorated eating and marketing quality [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that peanut cultivars and breeding lines having smaller seed size or rapid growth rate could be economically efficient for getting higher sprout yields. Some of the cultivars and breeding lines had excessive sprout growth on day 8 and 9 which showed deteriorated eating and marketing quality [20].…”
Section: Resultsmentioning
confidence: 99%
“…Miao et al [12] obtained optimum resveratrol content in the peanut sprouts on day 5. Lee et al [20] found the highest resveratrol content on day 9. Kang et al [23] reported the total polyphenol and antioxidant activities of peanut sprouts on 9 days.…”
Section: Resveratrol Contentmentioning
confidence: 95%